Preventing Violations of Religious and Social Norms: Judicial Interpretation of 'Urgent Reasons' in Marriage Dispensation at the Wonosari Religious Court, Indonesia - Rohman, Taufiqur; Mahsus, Muhammad; Abduh, Muhammad; Arnone, Gioia (Institut Agama Islam Negeri (IAIN) Pontianak, 2023)
Early marriage in Indonesia has garnered attention from international forums, urging the eradication of this practice to safeguard children’s rights. Despite national regulations raising the minimum age of marriage to 19 for both males and females, this practice persists due to legal loopholes allowing marriage dispensations granted by the court. Utilizing a socio-legal approach, this article analyzes 14 verdicts from the Wonosari Religious Court in 2022. The authors find that religious judges employ juridical, theological, psychological, and sociological argumentations in approving marriage dispensations based on three reasons presented by applicants. Among these reasons, two are granted not based on ‘urgent reasons’ but rather on interpretations of Islamic law and prevailing social norms. In-depth interviews with four religious judges handling these cases reveal variations in interpreting ‘urgent reasons’ in the context of marriage dispensations. The authors argue that the interpretation of ‘urgent reasons’ should prioritize the best interests of the child rather than merely considering potential violations of religious and social norms. This study provides profound insights into the dynamics of legal interpretation in the marriage dispensation decision-making process.